Desain Rekayasa dan Analisis Fea Alat Pengering Maggot Tipe Microwave Conveyor - Didit Wijang Saputro; Ikhwan Taufik; Tri Retno Setiyawati; Arif Rahman Saleh (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
One method of drying Black Soldier Fly (BSF) larvae that can be applied is drying using a continuous microwave oven. This tool utilizes microwaves emitted to evaporate water. In addition, the use of a conveyor that runs on a microwave oven as a medium or place to place BSF larvae is expected to simplify the production process. This study was conducted to determine the design and strength analysis of the thermal structure of a continuous microwave oven-type BSF larva dryer using Solidworks software. The specifications of the continuous microwave oven-type BSF larva dryer have a capacity of 15 kg, a heating input power of 8 KW and a temperature of 100℃. With variations in heating time of 20, 30, and 40 minutes. The results of the thermal structure analysis of the BSF larva dryer type continuous microwave oven based on the simulation obtained stress with the highest value of and the lowest value of . The results of the displacement simulation with the highest value of and the lowest value of . The Safety factor simulation result is 3.2. So from the simulation results it can be said that it is safe to continue to the manufacturing process.